Young Big Jake - Sargent, Dave, 1941-; Sargent, Pat, 1936-; Woodward, Elaine (Prairie Grove, AR : Ozark Pub., 2005)
Big Jake, a baby mouse, has a frightening encounter with a chicken hawk.
"A character development book"--Cover.
0.7
K-3
Keywords: Mice -- Fiction; Animals -- Infancy -- Fiction; Mice -- Fiction; Animal babies -- Fiction